Comparison of pelvic floor dysfunction in primiparous and nulliparous women and its relation to pelvic floor muscle strength - Naghma, Shahida; Batra, Achla; Kumar, Deepak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The pelvic floor muscles (PFM) play an important role in supporting the pelvic and abdominal organs and controlling urinary and fecal continence, in addition to their role in the sexual function. The objective of this study was to compare pelvic floor muscle strength in primiparous 6 months after delivery and nulliparous women, to evaluate pelvic floor dysfunction (PFD) in these women and to find the association of PFD with pelvic floor muscle strength (PFMS). Methods: A total of 100 women were recruited in the cross-sectional study which included 28 nulliparous and 72 primiparous women 6 months after delivery. The assessment included general physical examination (GPE), POP-Q and assessment of pelvic floor muscle strength by modified oxford score and perineometer. Results: Endurance of PFMS measured by duration of contraction and number of contractions/min was higher in nulliparous. Mean of the duration of contraction was significantly higher in nulliparous group as compared to primipara i.e., 28.61 seconds and 23.9 seconds in nulliparous and primiparous group respectively (p=0.005). Mean of the number of contractions performed in one minute was significantly higher in nulliparous group as compared to primipara i.e., 31.04 and 19.97 in nulliparous and primiparous group respectively (p<0.0001). None of the nulliparous women had any PFD symptoms, while 4.17% of the primiparous patients had PFD in the form of bladder symptoms and 1.39% of them had PFD in the form bowel symptoms. Vaginal squeeze pressure was found to be affected by mode of delivery. It was lowest in instrumental delivery. It was 39.78±13.33 cmH20 in vaginal delivery, 51.42±12.88 cmH2O in Caesarean section and 31.67±14.36 cmH2O in instrumental delivery (p-0.039). Conclusions: Endurance of PFMS measured by duration of contraction and number of contractions/min was higher in nulliparous. Vaginal squeeze pressure was found to be affected by mode of delivery. It was lowest in instrumental delivery.